The public health control of scabies: priorities for research and action. Issue 10192 (6th July 2019) - Engelman, Daniel; Cantey, Paul T; Marks, Michael; Solomon, Anthony W; Chang, Aileen Y; Chosidow, Olivier; Enbiale, Wendemagegn; Engels, Dirk; Hay, Roderick J; Hendrickx, David; Hotez, Peter J; Kaldor, John M; et al.
Summary: Scabies is a parasitic disease of the skin that disproportionately affects disadvantaged populations. The disease causes considerable morbidity and leads to severe bacterial infection and immune-mediated disease. Scientific advances from the past 5 years suggest that scabies is amenable to population-level control, particularly through mass drug administration. In recognition of these issues, WHO added scabies to the list of neglected tropical diseases in 2017. To develop a global control programme, key operational research questions must now be addressed. Standardised approaches to diagnosis and methods for mapping are required to further understand the burden of disease. The safety of treatments for young children, including with ivermectin and moxidectin, should be investigated. Studies are needed to inform optimum implementation of mass treatment, including the threshold for intervention, target, dosing, and frequency. Frameworks for surveillance, monitoring, and evaluation of control strategies are also necessary.